Design and fabrication of a die for molding test press. - Mohd Sabri, Hussin; Mohd Fidzwan, Md Amin Hamzas; M. J., Hasnul; Zailani, Zainal Abidin; Asmawi, Sanuddin (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com